1982
DOI: 10.3109/00498258209038955
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic properties of allylic and α,β-unsaturated compounds: Consideration of alkylating mechanisms

Abstract: 1. Allyl and allylic compounds may exert alkylating activities by SN1, SN2 and SN2' mechanisms. This direct alkylating potential can be determined quantitatively by a modified 4-NBP (4-nitrobenzyl pyridine) test. 2. The alkylating activities in a systematically selected series of allyl and allylic compounds correlate well with the direct mutagenic potential as determined in the Ames test using Salmonella typhimurium TA 100 as tester strain. 3. The allylic structure is a prerequisite for these types of activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(76 citation statements)
references
References 19 publications
3
73
0
Order By: Relevance
“…a,,B-Unsaturated carbonyl compounds are also used as pesticides or formed as degradation products of pesticides (4,5). Since our group first published structure mutagenicity relationships for these compounds (6)(7)(8), many other studies have confirmed that these compounds are mutagenic (9)(10)(11). Cro- tonaldehyde has been found to induce liver cancer in rats (12), and it should be considered as a potential human carcinogen.…”
mentioning
confidence: 99%
“…a,,B-Unsaturated carbonyl compounds are also used as pesticides or formed as degradation products of pesticides (4,5). Since our group first published structure mutagenicity relationships for these compounds (6)(7)(8), many other studies have confirmed that these compounds are mutagenic (9)(10)(11). Cro- tonaldehyde has been found to induce liver cancer in rats (12), and it should be considered as a potential human carcinogen.…”
mentioning
confidence: 99%
“…9 The Panel noted that the publication of Eder et al, 1982 is not the correct paper to quote from. It has not been possible for EFSA to identify the correct paper.…”
Section: Subgroup I (Acyclic Sulphides)mentioning
confidence: 99%
“…The supporting substances are listed in brackets. (Smyth et al, 1970) Rat NR 8930 (Smyth et al, 1969b) Rat NR 9750 (FDA, 1975a) Rat NR 6800 (Kimura et al, 1971a) Rat NR 3465 (Kohli et al, 1967) Mouse M 5250 (Tanii et al, 1986) Rabbit NR 5300 (Krasavage et al, 1982) (Isopropyl alcohol [02.079]) Rat NR 5840 (Smyth & Carpenter, 1948) Rat NR 5280 (Lehman & Chase, 1944) Rat NR 5300 (Kimura et al, 1971a) Rat NR 5330 (FDA, 1975a) Mouse NR 5070 (FDA, 1975a) Rabbit NR 5040 (Lehman & Chase, 1944) Rabbit NR 7990 (Munch, 1972) Dog NR 4830 (Lehman & Chase, 1944) (2-Butanone [07.053]) Rat M 5490 (Smyth et al, 1962) Rat NR 2730 (Kimura et al, 1971a) Rat NR 3980 (Union Carbide Corp., 1956) Rat F 5525 (Pozzani et al, 1959) Mouse M 3137 (Zakhari et al, 1977) Mouse M 4050 (Tanii et al, 1986) (2-Pentanone [07.054]) Rat M 3730 (Smyth et al, 1962) The EFSA Journal (2009) 1020, 53-70 (Tanii et al, 1986) (2-Pentanol [02.088]) Rabbit NR 2820 (Munch, 1972) Pentan-3-one [07.084] Rat NR 2900 (BASF, 1969) Rat NR 2140 (Panson & Winek, 1980) Rat NR 2140 (Eder et al, 1982a) Rat NR 2140 (Kennedy & Graepel, 1991) Rat NR 3100 (Ibatullina & Larionova, 1997) Pentan-3-ol [02.077] Rat NR 1870 (Eder et al, 1982a) ( (Schafer & Bowles, 1985) Mouse M 5460 (Tanii et al, 1986) Methyl-3-butan-2-one [07.178] Mouse M 2572 (Tanii et al, 1986) Rat NR 148 (Kennedy & Graepel, 1991) (4-Methyl-2-pentanone [07.017]) Rat NR 2080 (Smyth et al, 1951a) Mouse M 2670 (Tanii et al, 1986)...…”
Section: Annex Iv: Toxicitymentioning
confidence: 99%